2012
DOI: 10.1002/icd.1757
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Facial Characteristics Differentiate Communicative Intent of Infant‐Directed Speech

Abstract: Adults and infants can differentiate communicative messages using the nonlinguistic acoustic properties of infant‐directed (ID) speech. Although the distinct prosodic properties of ID speech have been explored extensively, it is currently unknown whether the visual properties of the face during ID speech similarly convey communicative intent and thus represent an additional source of social information for infants during early interactions. To examine whether the dynamic facial movement associated with ID spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
(67 reference statements)
1
12
0
Order By: Relevance
“…The question remains as to why ID style facilitates the processing of auditory-visual fluent speech more than AD style does. One speculation is that the characteristic auditory (or acoustic) and visual (or articulatory) properties of ID speech (Fernald & Kuhl, 1987;Shepard et al, 2012) improve infants' attention to speech cues and are easier to process (Soderstrom, 2007). It has also been shown that ID speech elicits increased neural activity compared to AD speech in 6-and 13-month-olds for familiar words (Zangl & Mills, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The question remains as to why ID style facilitates the processing of auditory-visual fluent speech more than AD style does. One speculation is that the characteristic auditory (or acoustic) and visual (or articulatory) properties of ID speech (Fernald & Kuhl, 1987;Shepard et al, 2012) improve infants' attention to speech cues and are easier to process (Soderstrom, 2007). It has also been shown that ID speech elicits increased neural activity compared to AD speech in 6-and 13-month-olds for familiar words (Zangl & Mills, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Note that our attempts to control smiling in the current stimuli do not rule out the possibility that the speaker's face is more dynamic in general when producing IDS. From the second experiment in Shepard et al (2012), authors conclude that moving faces of adults speaking IDS provide cues about emotion or intentions. The IDS stimuli in their experiment were made from recordings of speakers asked to provide realistic samples of the way adults speak to infants, implying long stretches of speech, with ample time for perceivable face movement.…”
Section: Fixation Times and Idsmentioning
confidence: 98%
“…She was audio-, and video-recorded while completing ten repetitions of each of the CV-syllables /pa:/, /pi:/ and /pu:/ while sitting face-to-face with the listener. Studies of head movement in IDS have evaluated translation and rotation of the head in ADS and IDS and although one study observed more head movement in ADS compared to IDS (Shepard, Spence & Sasson, 2012), it has more widely been found that mothers move their heads more when speaking to their infants than when speaking to an adult (Smith & Strader, 2014). For this reason, the mother was instructed to avoid moving her head when articulating the syllables.…”
Section: Experimental Stimulimentioning
confidence: 99%
“…Compared to adult-directed speech (ADS), IDS to infants with NH has shorter and grammatically simplified utterances (Kavanaugh & Jirkovsky, 1982;Phillips, 1973;Snow, 1977), a higher proportion of questions (Soderstrom et al, 2008), increased repetition, longer duration of vowels and pauses , slower speech rate (Fernald & Simon, 1984), greater positive affect (Fernald & Kuhl, 1987;Uther et al, 2007), greater pitch (fundamental frequency, F0) variations (McRoberts & Best, 1997), and exaggerated articulation of speech sounds (Burnham et al, 2002;Kuhl et al, 1997). In addition, in the visual modality, facial movements made in producing IDS differ from those in ADS (Chong et al, 2003;Shepard et al, 2012), with IDS showing characteristics such as exaggerated lip SPEECH TO INFANTS WITH HEARING LOSS 12 movements (Green et al, 2010), exaggerated smiles, increased eyebrow raising, and greater eye widening (Werker & McLeod, 1989).…”
Section: Quality Of Language Input: Infant-directed Speech Acoustic and Phonetic Featuresmentioning
confidence: 99%